2014
DOI: 10.1002/pip.2485
|View full text |Cite
|
Sign up to set email alerts
|

Gallium gradients in Cu(In,Ga)Se2thin-film solar cells

Abstract: The gallium gradient in Cu(In,Ga)Se2 (CIGS) layers, which forms during the two industrially relevant deposition routes, the sequential and co‐evaporation processes, plays a key role in the device performance of CIGS thin‐film modules. In this contribution, we present a comprehensive study on the formation, nature, and consequences of gallium gradients in CIGS solar cells. The formation of gallium gradients is analyzed in real time during a rapid selenization process by in situ X‐ray measurements. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
103
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 68 publications
(85 reference statements)
4
103
1
Order By: Relevance
“…However, alkali-metal doping also happens to hinder In/Ga interdiffusion in polycrystalline CIGS films. The effect was observed almost regardless of the alkali metal incorporation source 6,19–26 . This behaviour is ascribed to a reduction of the concentration of Cu vacancies (V Cu ) following Na addition.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, alkali-metal doping also happens to hinder In/Ga interdiffusion in polycrystalline CIGS films. The effect was observed almost regardless of the alkali metal incorporation source 6,19–26 . This behaviour is ascribed to a reduction of the concentration of Cu vacancies (V Cu ) following Na addition.…”
Section: Introductionmentioning
confidence: 93%
“…In order to take advantage of a favourable band structure, CIGS devices are typically produced with a v-shaped Ga depth gradient that increases the collection of photogenerated electrons while reducing recombination at the CIGS/CdS interface 4,5 . Recent simulations have shown that the resulting trade-off between short circuit current and open circuit voltage depends on the position of the minimum (notch) in the Ga depth profile 6 . As a consequence, the efficiency could be further improved by shifting the notch position closer to the absorber surface, compared to recent record efficiency devices 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] A V-shaped Ga gradient which can increase the collection efficiency of photogenerated electrons and maintain a decent open circuit voltage of the solar cell has been widely accepted for the fabrication of high-efficiency CIGS solar cells. 34,35 The study of the above two topics has contributed to the improvement of the conversion efficiency of CIGS solar cells, however, the un-addressed mechanism of these two questions may have accounted for a large portion of the nonreproducibility of CIGS solar cells observed in many laboratories, rendering the industrialization process of CIGS far behind CdTe solar cells, even though the world record conversion efficiency of CIGS is higher. However, the formation mechanism of Ga gradient is still in debate.…”
Section: Introductionmentioning
confidence: 99%
“…In CIGSe, this type of gradient leads to substantial improvements of open-circuit voltage (V oc ) and charge carrier collection. 4,5 Current efficiency levels of kesterites are below 13%, 6 because of short minority carrier lifetimes in the sub-nano-second regime. 7 Kesterite compounds like Cu 2 Zn(Sn,Ge)(S,Se) 4 as absorber for thin-film solar cells have the potential to contribute to the increase of solar energy in large volumes using earthabundant elements such as Sn and Zn.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Current efficiency levels of kesterites are below 13%, 6 because of short minority carrier lifetimes in the sub-nano-second regime. 7 Kesterite compounds like Cu 2 Zn(Sn,Ge)(S,Se) 4 as absorber for thin-film solar cells have the potential to contribute to the increase of solar energy in large volumes using earthabundant elements such as Sn and Zn. The capability of these compounds to host various elements in the same atomic position, such as Sn and Ge in Cu 2 Zn(Sn,Ge)Se 4 (CZTGeSe), allows tuning of the band gap of the compound by varying the composition similar to CIGSe.…”
Section: Introductionmentioning
confidence: 99%